1996
DOI: 10.1042/bj3170141
|View full text |Cite
|
Sign up to set email alerts
|

Probing the S-adenosylmethionine-binding site of rat guanidinoacetate methyltransferase. Effect of site-directed mutagenesis of residues that are conserved across mammalian non-nucleic acid methyltransferases. Effect of site-directed mutagenesis of residues that are conserved across mammalian non-nucleic acid methyltransferases

Abstract: Most mammalian non-nucleic acid methyltransferases share three sequence motifs. To gain insight into the S-adenosyl-methionine (AdoMet)-binding site of guanidinoacetate methyltransferase, we mutated several conserved residues that are found in or near motifs I and II. Conversion of either of two glycine residues of motif I (Gly67 and Gly69) to an alanine resulted in an inactive enzyme. These enzymes, although having UV absorption, fluorescence and far-UV CD spectra virtually identical with those of the wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 34 publications
2
27
0
1
Order By: Relevance
“…We observed R h values ranging from 6.1 to 7.5 nm for TehB(Phe98Tyr), which suggests that this particular mutant either is more susceptible to aggregation or oligomerizes into a decamer. The other mutants showed no change with SAM and tellurite binding, which is in agreement with studies of motifs I and II of a rat non-nucleic acid methyltransferase examined by a variety of spectroscopic methods (22). The study observed only minor conformational changes with mutations to key residues and concluded that the SAM-binding site has strict residue requirements.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…We observed R h values ranging from 6.1 to 7.5 nm for TehB(Phe98Tyr), which suggests that this particular mutant either is more susceptible to aggregation or oligomerizes into a decamer. The other mutants showed no change with SAM and tellurite binding, which is in agreement with studies of motifs I and II of a rat non-nucleic acid methyltransferase examined by a variety of spectroscopic methods (22). The study observed only minor conformational changes with mutations to key residues and concluded that the SAM-binding site has strict residue requirements.…”
supporting
confidence: 85%
“…Aromatic rings are considered to be involved in binding SAM through cation-quadrapole interactions with the positively charged sulfonium moiety of SAM (13,31). The importance of tyrosine in motif II of rat guanidinoacetate methyltransferase (RGAMT) has already been demonstrated (22). In TehB, four aromatic residues were found in this region; they are Phe (Ϫ5 position with respect to Asp), Tyr (Ϫ1), Phe (ϩ1), and Phe (ϩ10).…”
mentioning
confidence: 99%
“…Considering the data together, it is evident that the cofactor interacts with homologous sequence elements within the cofactor-binding site of the N-MTase domains of distinct NRPS systems. Furthermore, both studies are in line with a study of rat guanidinoacetate MTase, which identified a Tyr residue within the AdoMet-binding motif II region of this enzyme as forming the covalent adduct with AdoMet (50,51). The recent resolution of the crystal structure of rat guanidinoacetate MTase revealed that this residue is proximal to the AdoMet binding pocket of this enzyme (52).…”
Section: Discussionsupporting
confidence: 60%
“…These sequences conform to the general consensus for motif I (hh(D/E)hGXGXG), where h is a hydrophobic amino acid, X is any amino acid, and the position of glycine residues is strongly conserved (49). Motif I has been associated with the binding of AdoMet by the enzyme and mutation of the conserved glycine residues in motif I in guanidinoacetate methyltransferase abolished its catalytic activity (50). An acidic residue which contributes to the binding of AdoMet has been found between 17 and 19 residues C-terminal to the end of motif I (48,50).…”
Section: Discussionmentioning
confidence: 99%
“…Motif I has been associated with the binding of AdoMet by the enzyme and mutation of the conserved glycine residues in motif I in guanidinoacetate methyltransferase abolished its catalytic activity (50). An acidic residue which contributes to the binding of AdoMet has been found between 17 and 19 residues C-terminal to the end of motif I (48,50). In S-adenosyl-L-methionine:arsenic(III) methyltransferase and human Cyt19, aspartate was found 20 residues C-terminal to the end of motif I.…”
Section: Discussionmentioning
confidence: 99%